Association between Statin Use and Sepsis Risk in Patients with Dementia: A Retrospective Cohort Study - Yeh, Liang-Tsai (Int J Environ Res Public Health, 2019)
This study investigated the association of statin use with sepsis risk in patients with dementia. This retrospective cohort study was conducted in Taiwan by using data from the National Health Insurance Research Database. We identified and enrolled 308 patients with newly diagnosed dementia who used statin after dementia diagnosis. These patients were individually propensity score matched (1:1) according to age, sex, hypertension, hyperlipidemia, diabetes, cerebrovascular disease, renal disease, liver disease, asthma, malignancy, parkinsonism, and dementia drugs used (donepezil, rivastigmine, galantamine, and memantine) with 251 controls (statin non-users). A Cox proportional hazard model was used to estimate the adjusted hazard ratio for sepsis in statin users and non-users. After adjustment for other confounding factors, the incidence of sepsis in statin users was 1.42-fold higher than that in non-users (95% confidence interval = 0.81–2.5). In conclusion, our analysis showed no positive association of sepsis with statin use in patients with dementia.